Evolving food value chains - Minten, Bart; Dereje, Mekdim; Bachewe, Fantu Nisrane; Tamru, Seneshaw (International Food Policy Research Institute, 2020)
The second part of the book, “Evolving Markets and Household Consumption,” begins with Chapter 7 on “Evolving Food Value Chains.” Ethiopia’s food systems are changing rapidly as high population growth, rapid urbanization, major infrastructure investments, and substantial income growth are leading to dietary, agricultural, and supply chain transformations. Over the past two decades, calorie consumption has risen, the share of starchy staples in the diet has fallen, and the shares of high-value products (such as animal-sourced foods, fruits and vegetables, processed convenience foods, and out-of-home food consumption) have risen. At the same time, use of fertilizer, improved seeds, and mechanization is increasing. Nonetheless, smallholders, who have an average agricultural area of 1.0 hectare per holder and who cultivate 93 percent of the agricultural land in Ethiopia, are facing increasing land constraints: farm sizes are declining over time and, in comparison to older farmers, younger farmers are more reliant on land rental markets to access the land that they farm. The transformation of agricultural supply chains is especially rapid, providing for increases in employment. Agricultural commercial surpluses are rapidly growing, and modern food marketing methods and technologies have emerged, including mobile phones, a commodity exchange, and an incipient modern retail sector and food service sector. Domestic markets are better integrated as spatial and seasonal price margins have narrowed. External trade has also expanded since 2000 despite high transport costs and foreign exchange restrictions.